Development of Truth or Dare Card Media on Pancasila Values Material for Grade V Elementary School Students - Alifah Nur Aini; Eddy Noviana; Munjiatun (Education Generation Journal, 2024)
This study aims to determine the level of validity and practicality of the Truth or Dare card media on the material of Pancasila values for grade V of SDN 105 Pekanbaru. This type of research is Research and Development (RnD). The development of the Truth or Dare card media was carried out using the 4D model consisting of the define, design, develop, and disseminate stages. The results of the study. showed that the validation results from the experts showed that the Truth or Dare card media on the material of Pancasila values for grade V elementary school students was very feasible to use. Based on the analysis of the expert assessment, namely media experts with an average of 91.5%, material experts 97.5% and language experts 83.3%, teacher responses 100%, student responses 91.4%. The results of the effectiveness test showed a percentage value between 5-6 with an average N gain effectiveness interpretation of 0.65 and can be said to be effective. It can be concluded that the product "Development of Truth or Dare Card Media on Pancasila Values Material for Grade V Elementary School" developed is declared valid and can be used practically as a PPKn learning media in Grade V Elementary School